PIM findings on designing cash transfers to reduce intimate partner violence influence the design of World Bank social protection operations, including grants for a total of USD 167M to the Government of Mozambique - CGIAR Research Program on Policies, Institutions, and Markets (2021)
PIM research on how to design cash transfer programs to reduce intimate partner violence are taken up by World Bank teams to design safety nets in Mozambique, Guinea and Papua New Guinea. Both the Mozambique Project Appraisal Document for a grant for the Social Protection and Economic Resilience project in Mozambique and the World Bank Safety First operational guide cite PIM research.